Development of Nation State of Malaysia Based on Mahathir Mohamad’s Leadership Model Framework - et. al., Khairul Azman Mohamad Suhaimy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Each Prime Minister has his or her own leadership and achievements while leading the development of the nation-state. Mahathir Mohamad's leadership and achievements in driving Malaysia's modernization are well known because the effort has succeeded in benefiting Malaysians so that he can be appointed as the Father of Malaysian Modernization. The effectiveness of his leadership can be assessed based on the achievements that have been successfully achieved by the country through the implementation of actions and policies that he led throughout leading the country. Therefore, this article aims to discuss the elements of Mahathir's leadership by tracing his leadership when implementing actions and policies to modernize Malaysia so that it can achieve a proud achievement in the context of the development of the Malaysian nation. This study uses the method of document analysis by analyzing the text of Mahathir's speech as the main source and applying thematic analysis as an analysis approach. The text of the speech was analyzed thematically to identify the themes that exist and refer to the elements of leadership applied by him throughout the implementation of actions and policies to modernize the country. The results of the analysis show that there are 11 elements of leadership practiced by Mahathir such as injecting intellectual, injecting motivation, practicing good values in governing, valuing togetherness, exhibiting ideal influence, organized in leadership, assertive in leading, far-sighted, considerate of each individual, appreciating the contribution of the people, and confident in the ability to lead. Indirectly, the results of the analysis reflect that a country can achieve a proud achievement in the process of modernization if the country's leaders practice certain elements of leadership. The implications of this study, first, reflect the importance of a leader's leadership evaluation based on the achievements that have been achieved because it can identify a set of leadership elements practiced by the leader. Second, it reflects the importance of the role of leaders in determining and shaping the definition of nation-state development that should be highlighted in a country. The contribution of this study is to introduce a leadership model framework based on Mahathir's achievements throughout his administration of the Malaysian nation. In addition, it gives an overview of the elements of his leadership as a successful national leader. This leadership model framework is also suitable to be applied by leaders or related parties involved or interested in leadership-related discussions.